Ligation of newly replicated DNA controls the timing of DNA mismatch repair - Reyes, Gloria X.; Kolodziejczak, Anna; Devakumar, Lovely Jael Paul Solomon; Kubota, Takashi; Kolodner, Richard D.; Putnam, Christopher D.; Hombauer, Hans (Current biology, 2021)
Mismatch repair (MMR) safeguards genome stability through recognition and excision of DNA replication errors.1, 2, 3, 4 How eukaryotic MMR targets the newly replicated strand in vivo has not been established. MMR reactions reconstituted in vitro are directed to the strand containing a preexisting nick or gap,5, 6, 7, 8 suggesting that strand discontinuities could act as discrimination signals. Another candidate is the proliferating cell nuclear antigen (PCNA) that is loaded at replication forks and is required for the activation of Mlh1-Pms1 endonuclease.7, 8, 9 Here, we discovered that overexpression of DNA ligase I (Cdc9) in Saccharomyces cerevisiae causes elevated mutation rates and increased chromatin-bound PCNA levels and accumulation of Pms1 foci that are MMR intermediates, suggesting that premature ligation of replication-associated nicks interferes with MMR. We showed that yeast Pms1 expression is mainly restricted to S phase, in agreement with the temporal coupling between MMR and DNA replication.10 Restricting Pms1 expression to the G2/M phase caused a mutator phenotype that was exacerbated in the absence of the exonuclease Exo1. This mutator phenotype was largely suppressed by increasing the lifetime of replication-associated DNA nicks, either by reducing or delaying Cdc9 ligase activity in vivo. Therefore, Cdc9 dictates a window of time for MMR determined by transient DNA nicks that direct the Mlh1-Pms1 in a strand-specific manner. Because DNA nicks occur on both newly synthesized leading and lagging strands,11 these results establish a general mechanism for targeting MMR to the newly synthesized DNA, thus preventing the accumulation of mutations that underlie the development of human cancer.